3D wavefield tomography: Synthetic and field data examples - Warner,M; Stekl,I; Umpleby,A (Seg Technical Program Expanded Abstracts, 2008)
Full wavefield tomography has become well established in two dimensions, but its extension into 3D for realistically sized problems is computationally daunting. In this paper, we present one of the first studies to apply 3D wavefield tomography to field data, and demonstrate that the method can solve useful exploration problems that that are not tractable by other methods.